Physician‒Scientists in Italian Dermatology: Hurdles and Perspectives - Carlo Pincelli; Antonio Costanzo (Elsevier, 2022)
Physicians, including dermatologists, with expertise in clinical and basic research, play a pivotal role in the advancement of medical science. Although the number of residents in dermatology has been increasing and our specialty is among the most requested in Italy, the disaffection of young dermatologists for research is a chronic and apparently irreversible trend. This commentary analyzes the reasons and suggests some ideas to counteract this alarming tendency.